Mini automatic guided vehicle using peripheral interface controller: article - Selamat, Muhammad Zuwairi (2006)
Automatic Guided Vehicles (AGVs) system has been in existence since 1953. It begins with the vehicles to follow the imbedding a wire in the factory floor. Today the technology continues to evolve. The wire in the floor is still available for the proper application. However, many systems today are being designed without the floor wire. This paper is concern about the development a prototype of AGVs called Mini Automatic Guided Vehicle (Mini AGV) with a sophisticated technique in tracking the path on the floor. It involved software development for the system to give a view on how the real operation of AGVs in the industry. All these system will be controlled by the Peripheral Interface Controller (PIC) microcontroller.